Pathogenic WDFY3 variants cause neurodevelopmental disorders and opposing effects on brain size - Le Duc, Diana; Giulivi, Cecilia; Hiatt, Susan M.; Napoli, Eleonora; Panoutsopoulos, Alexios; Harlan De Crescenzo, Angelo; Kotzaeridou, Urania; Syrbe, Steffen; Anagnostou, Evdokia; Azage, Meron; Bend, Renee; Begtrup, Amber; et al. (Brain, 2019)
The underpinnings of mild to moderate neurodevelopmental delay remain elusive, often leading to late diagnosis and interventions. Here, we present data on exome and genome sequencing as well as array analysis of 13 individuals that point to pathogenic, heterozygous, mostly de novo variants in WDFY3 (significant de novo enrichment P = 0.003) as a monogenic cause of mild and non-specific neurodevelopmental delay. Nine variants were protein-truncating and four missense. Overlapping symptoms included neurodevelopmental delay, intellectual disability, macrocephaly, and psychiatric disorders (autism spectrum disorders/attention deficit hyperactivity disorder). One proband presented with an opposing phenotype of microcephaly and the only missense-variant located in the PH-domain of WDFY3. Findings of this case are supported by previously published data, demonstrating that pathogenic PH-domain variants can lead to microcephaly via canonical Wnt-pathway upregulation. In a separate study, we reported that the autophagy scaffolding protein WDFY3 is required for cerebral cortical size regulation in mice, by controlling proper division of neural progenitors. Here, we show that proliferating cortical neural progenitors of human embryonic brains highly express WDFY3, further supporting a role for this molecule in the regulation of prenatal neurogenesis. We present data on Wnt-pathway dysregulation in Wdfy3-haploinsufficient mice, which display macrocephaly and deficits in motor coordination and associative learning, recapitulating the human phenotype. Consequently, we propose that in humans WDFY3 loss-of-function variants lead to macrocephaly via downregulation of the Wnt pathway. In summary, we present WDFY3 as a novel gene linked to mild to moderate neurodevelopmental delay and intellectual disability and conclude that variants putatively causing haploinsufficiency lead to macrocephaly, while an opposing pathomechanism due to variants in the PH-domain of WDFY3 leads to microcephaly.
CRIS-Team Scopus Importer:2019-09-17
Keywords: WDFY3; brain size; intellectual disability; neurodevelopmental delay